Differences in biologic dose-escalation, non-biologic and steroid intensification among three anti-TNF agents: evidence from clinical practice - MOOTS, R. J; HARAOUI, B; SINGH, A; MATUCCI-CERINIC, M; VAN RIEL, P. L. C. M; KEKOW, J; SCHAEVERBEKE, T; DAVIS, A; TEDESCHI, M. A; FREUNDLICH, B; CHANG, D. J (Clinical and experimental rheumatology, 2011)
To evaluate prevalence of dose escalation among RA patients in normal clinical practice treated with etanercept, adalimumab or infliximab and to estimate its economic impact. A retrospective observational study of 739 patients with RA receiving continuous treatment with etanercept (n=319), adalimumab (n=313) or infliximab (n=107) for 18 months. Dose escalation, intensification of concomitant DMARDs and risk of dose escalation were evaluated, as well as costs. Significantly more patients prescribed adalimumab (10%, p<0.001) or infliximab (35%, p<0.001) experienced dose escalation compared with patients treated with etanercept (3%). DMARD or steroid dose adjustment, when added as criteria of escalation, occurred more often among patients treated with adalimumab (28%; p=0.022) or infliximab (47%; p<0.001) than those prescribed etanercept (19%). Independent of confounding covariates, hazard of dose escalation was significantly higher for either infliximab (28.1-fold) or adalimumab (4.9-fold) relative to etanercept. Escalation among subjects treated with either infliximab or adalimumab incurred statistically significant increases in total cost of care compared with non-escalators whereas such differences observed for subjects treated with etanercept were not significant. Patients receiving monoclonal antibody therapies, adalimumab or infliximab, had significantly higher rates of dose escalation than patients receiving the soluble TNF receptor, etanercept, and related costs were higher.